Dynamic monitoring of cognitive impairment and prognostic recurrence in patients with stroke by serum HDAC3 and FOXO1: a new diagnostic method - Li, Xintong; Wang, Lulu; Xiao, Bin; Liu, Zhengkun; Dou, Yue (Journal of Medical Biochemistry, 2025)
Objective: To evaluate the clinical value of dynamically monitoring serum histone deacetylase 3 (HDAC3) and forkhead box protein O1 (FOXO1) levels in evaluating cognitive impairment (CI) in cerebral stroke (CS) patients, so as to facilitate early identification of high-risk individuals and guide targeted interventions.Methods: This study included 120 CS patients admitted from March, 2023 to March, 2024, with their serum HDAC3 and FOXO1 levels examined upon admission (T0) and at 2 (T1) and 24 hours (T2) following treatment. Differences in biomarker levels (CI group vs. non-CI group) were analyzed, and the predictive value of HDAC3 and FOXO1 for CI was determined. In addition, patients were followed up for 1 year prognosis, and the predictive effect of HDAC3 and FOXO1 on the prognostic recurrence of CS was analyzed.Results: CI occurred in 46 cases. HDAC3 expression was markedly increased in CI cases versus non-CI patients at T0, T1, and T2, whereas FOXO1 differed significantly only at T1 and T2 (P